2013
DOI: 10.1002/biof.1128
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus La5, Bifidobacterium BB12, and Lactobacillus casei DN001 modulate gene expression of subset specific transcription factors and cytokines in peripheral blood mononuclear cells of obese and overweight people

Abstract: Probiotics are believed to have interaction with immune cells through sustained effects on gene expression of different cytokines and transcription factors. The present randomized doubled-blind controlled clinical trial was performed recruiting 75 individuals with BMI 25-35, who were randomly assigned to the following three groups: Group 1 (n = 25) who consumed regular yogurt as part of a low calorie diet [RLCD], group 2 (n = 25) who received probiotic yogurt with a LCD [PLCD] and group 3 (n = 25) who consumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 45 publications
5
41
1
1
Order By: Relevance
“…In the reviewed studies, only Hariri et al [54] reported a significant decrease of DBP and SBP when participants took Lactobacillus and Bifidobacterium foods or supplements. Other studies [50,52,57,64] reported no significant differences in blood pressure. Also, Agerholm-Larsen et al [61] suggested that there was a significant decrease in SBP and a significant increase in DBP between the intervention group and the control group.…”
Section: Change Of Anthropometric Indicatorsmentioning
confidence: 98%
See 3 more Smart Citations
“…In the reviewed studies, only Hariri et al [54] reported a significant decrease of DBP and SBP when participants took Lactobacillus and Bifidobacterium foods or supplements. Other studies [50,52,57,64] reported no significant differences in blood pressure. Also, Agerholm-Larsen et al [61] suggested that there was a significant decrease in SBP and a significant increase in DBP between the intervention group and the control group.…”
Section: Change Of Anthropometric Indicatorsmentioning
confidence: 98%
“…In terms of sample size calculation, 8 RCT studies did not report any type of power calculations [42,47,49,50,52,54,55,61]. One study reported post hoc calculation [66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently published meta-analysis found only 4 high-quality, randomized controlled studies comparing the therapeutic efficacy of probiotics with placebo and using body weight loss as the main end-point (table 1) [76,77,78,79]. The analysis of the pooled data failed to demonstrate significant differences in body weight, body mass index and mean visceral fat mass between the probiotic group and controls, therefore suggesting that probiotics are ineffective on body weight modulation [80].…”
Section: Gut Microbiota As Potential Therapeutic Target In Obesitymentioning
confidence: 99%